Developing a framework of gastronomic systems research to unravel drivers of food choice - Cuevas, Rosa Paula; de Guia, Annalyn; Demont, Matty (Elsevier, 2017)
Nutritional and dietary interventions and the introduction of novel food products and ingredients require a thorough understanding of the drivers of food choice, which are embedded in local context and culture. We develop a framework of “gastronomic systems research” (GSR) to understand culture-specific consumer food choice, and contextualise it to a target population of urban, middle- to high-income Filipino consumers to assess the domestic niche market potential of traditional rice varieties in the Philippines. The GSR framework is contextualised through expert elicitation involving chefs and nutritionists, and validated through a consumer survey conducted during a food exposition. Using the GSR framework, we determine indicative rice consumption patterns of the target population and the specific rice quality attributes they require for specific rice-based dishes and rice consumption occasions. The GSR framework also reveals possible entry points for nutritional and dietary interventions and the introduction of novel food products and ingredients. The GSR framework, therefore, has the potential to aid policymakers and food value chain stakeholders in designing culture-sensitive and context-appropriate interventions not only to help consumers improve their diets, but also to help farmers access niche markets for novel food products and ingredients and thereby improve their livelihoods and preserve cultural heritage